Association of APEX1 and XRCC1 Gene Polymorphisms With HIV-1 Infection Susceptibility and AIDS Progression in a Northern Chinese MSM Population - Liu, Bangquan; Wang, Kaili; Wu, Jiawei; Hu, Yuanting; Yang, Xun; Xu, Lidan; Sun, Wenjing; Jia, Xueyuan; Wu, Jie; Fu, Songbin; Qiao, Yuandong; Zhang, Xuelong (Frontiers in Genetics, 2022)
Background: Some studies have shown that the base excision repair (BER) pathway has an effect on HIV-1 replication. APEX1 and XRCC1 as key BER genes may affect DNA repair capacity. However, the roles of single nucleotide polymorphisms (SNPs) in APEX1 and XRCC1 and their impact on HIV-1 infection and AIDS progression remain unclear. Methods: A custom-designed 48-Plex SNPscan Kit was used for detection of single nucleotide polymorphisms. 601 HIV-1-infected men who have sex with men (MSM) and 624 age-matched healthy individuals were recruited in northern China. Four SNPs (rs1130409, rs1760944, rs2307486 and rs3136817) in APEX1 gene and three SNPs (rs1001581, rs25487 and rs25489) in XRCC1 gene were genotyped. The generalized multifactor dimension reduction (GMDR) method was used to identify the SNP-SNP interactions. Results: In this study, rs1130409 G allele, rs1001581 C allele and rs25487 C allele were associated with a higher risk of HIV-1 infection susceptibility (p = 0.020, p = 0.007 and p = 0.032, respectively). The frequencies of APEX1 haplotype TT and XRCC1 haplotype CT showed significant differences between cases and controls (p = 0.0372 and p = 0.0189, respectively). Interestingly, stratified analysis showed that the frequency of rs1001581 C allele was significantly higher in AIDS patients with the CD4+ T-lymphocyte count <200 cells/μl than those with >200 cells/μl (p = 0.022). Moreover, significant gene-gene interactions among rs1130409, rs1001581 and rs25487 were identified by GMDR (p = 0.0107). Specially, individuals with five to six risk alleles have a higher susceptibility to HIV-1 infection than those with zero to two risk alleles (p < 0.001). Conclusion:APEX1 and XRCC1 gene polymorphisms were associated with the susceptibility to HIV-1 infection and AIDS progression in MSM populations in northern China.